Ekstrak Serbuk Gergaji Kayu Eboni (Diospyros celebica Bakh.) Sebagai Fungisida Terhadap Phytophthora palmivora Butler. - Muhammad Alwi; Ramadhanil Ramadhanil; Dewa Nyoman Puspa (Biology Department, Mathematics and natural science, Tadulako University, 2010)
The research of potency of sawdusk ebony exstract as fungiside to Phytophthora palmivora Butler. in Basic Biology Laboratorium and Biotechnology Laboratorium at month Juni 2010. This research has purpose to know the extract effect of dust ebony (Diospyros celebica Bakh.) conserning with mushroom grouth (Phytophthora palmivora Butler.) and to get the concentration that efficient and effective, also to know the kind of resolvent that more effective, in this case are water and ethanol. This research use “Completely Randomized Design” pattern factorial. It can do by growing seet of the mushroom on PDA that have mixed with extract then, continued with the measurement of resistibility media from each treatment. Result of the research show that the extract of dust ebony can blocked the growth of mushroom colony Phytophthora palmivora Butler. that the best concentration is 5%, it can blocked 11 mm. and the efficient is 4%. If the extract concentration more high, so the capability for blocked the growth of mushroom colony more high too. Key words: Ebony, Phytophthora palmivora, and fungicide.